Bitva o život - Janek, Miroslav; Janeček, Vít; Vávra, Roman (Czech Republic : Verbascum ; Czech Television, 2000)
Using a mixture of documentary material they shot themselves, historical material and half-scripted scenes, the filmmakers show a year in the life of the village of Bystré, in the Orlické mountains, a former textile region experiencing significant economic and demographic change. The film combines "conventional" documentary footage with discussions on drink and democracy, and a record of social events and festivities in which the villagers greet the millennium, view the eclipse, and re-enact scenes from Czech history.
Keywords: Documentary films